A light-assisted solid-state lithium-air battery and preparation method thereof

By using NH2-MIL-125 metal organic frame material as photocatalyst and solid electrolyte in lithium air batteries, a solid-state photoair positive electrode can be constructed that can achieve ion/electron conduction and photocatalysis at the same time, solving the problems of battery energy conversion efficiency and stability in the prior art, and achieving efficient and stable battery performance.

CN114883705BActive Publication Date: 2025-03-28JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210586042.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-26
Publication Date
2025-03-28
Estimated Expiration
2042-05-26

AI Technical Summary

Technical Problem

In existing photo-assisted lithium air batteries, solid air positive electrodes cannot achieve ion/electron conduction and have photocatalytic capabilities at the same time, which limits the energy conversion efficiency and stability of the battery.

Method used

Using NH2-MIL-125 metal organic frame material as photocatalyst and solid electrolyte, a solid-state photoair positive electrode capable of simultaneously realizing ion/electron conduction and photocatalysis by introducing freely moving lithium ions into the pores was constructed.

Benefits of technology

It achieves ultra-low overpotential, high energy conversion efficiency and safe and stable long-term operation, improving the overall performance of lithium air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114883705B_ABST
    Figure CN114883705B_ABST
Patent Text Reader

Abstract

The present invention discloses a light-assisted solid-state lithium-air battery, which relates to the technical field of chemical power sources. The battery includes a negative lithium sheet, a solid electrolyte layer and a solid light-air positive electrode layer. The solid light-air positive electrode layer is supported by an ion / electron conductive material and uses an NH2-MIL-125 metal organic framework material with freely movable lithium ions in the pores as a photocatalyst. The solid electrolyte layer is made of an NH2-MIL-125 metal organic framework material with freely movable lithium ions, and forms a solid electrolyte-light-air positive electrode integrated material with the solid light-air positive electrode layer. The present invention constructs a solid light-air positive electrode of an ion / electron mixed conductor in a lithium-air battery for the first time, and designs a light-assisted solid-state lithium-air battery of an electrode-electrolyte integrated material to achieve ultra-low overpotential, high energy conversion efficiency, and safe and stable long-term operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical power sources, in particular to a light-assisted solid-state lithium-air battery and a preparation method thereof. Background Art

[0002] Electrochemical energy storage systems are of great strategic significance for the development of electric transportation and smart grids. Among them, lithium-air batteries have an ultra-high theoretical energy density and are one of the next-generation energy storage systems with great development potential. However, the slow reaction kinetics of lithium-air batteries, the decomposition of liquid electrolytes, and the lithium dendrites of the negative electrode limit their progress towards practical application. The development of efficient catalysts is an effective way to improve the reaction kinetics of batteries, but the energy conversion efficiency of batteries is still difficult to break through 80%. Recently, researchers have proposed an efficient light-assisted catalytic strategy to improve the reaction kinetics of batteries, thereby reducing the polarization degree of batteries and improving energy conversion efficiency. The core of this strategy is to design a reasonable photocatalyst as the photocathode of the battery. When the photocathode is exposed to light, the photocatalyst can absorb photons and generate a large number of separated photogenerated electrons and holes, which act on the charge and discharge process of the battery to promote the reversible electrochemical reaction.

[0003] Although the light-assisted lithium-air battery system has the above advantages, long-term illumination will inevitably accelerate the decomposition of the electrolyte, thereby causing a large number of side reactions and accelerating the failure of the battery. In order to replace organic liquid electrolytes, inorganic ceramic solid electrolytes, organic polymer solid electrolytes, molecular sieve solid electrolytes, etc. have been developed for the construction of solid-state lithium-air batteries. Therefore, this strategy is also expected to solve the problem of electrolyte decomposition in light-assisted lithium-air battery systems. The development of a new type of light-assisted solid-state lithium-air battery requires not only a solid electrolyte with high ion conductivity and air stability, but also a solid-state photo-air cathode that can simultaneously meet the requirements of electron / ion continuous conduction interface, abundant gas diffusion channels, and excellent light absorption efficiency. However, air-stable ion conductors are limited, and there is no previous research on light-responsive catalyst materials with simultaneous electron / ion conductivity for lithium-air batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a light-assisted solid-state lithium-air battery and a preparation method thereof, so as to solve the technical problem in the background technology that the solid-state air positive electrode cannot simultaneously achieve ion / electron conduction and have photocatalytic ability.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A light-assisted solid-state lithium-air battery comprises a negative lithium sheet, a solid electrolyte layer and a solid light-air cathode layer. The solid light-air cathode layer is supported by an ion / electron conductive material and uses an NH2-MIL-125 metal organic framework material having freely movable lithium ions in pores as a photocatalyst. The solid electrolyte layer is made of an NH2-MIL-125 metal organic framework material having freely movable lithium ions, and forms a solid electrolyte-light-air cathode integrated material with the solid light-air cathode layer.

[0007] On the basis of the above technical solution, the present invention also provides the following optional technical solution:

[0008] In an optional scheme: the NH2-MIL-125 metal organic framework material with freely movable lithium ions is prepared by exchanging an activated NH2-MIL-125 material, that is, an NH2-MIL-125 material with open metal sites, in a lithium salt solution.

[0009] In an optional solution: the NH2-MIL-125 material is prepared by a hydrothermal method, which specifically includes the following steps:

[0010] Step S1: adding a certain amount of 2-aminoterephthalic acid to a mixture of anhydrous methanol and N,N-dimethylformamide under stirring, and mixing evenly;

[0011] Step S2: slowly adding a certain amount of isopropyl titanate into the above-mentioned mixed solution under stirring, and vigorously stirring to obtain a uniform clear mixed solution;

[0012] Step S3: transferring the mixed solution obtained in step S2 to a reactor for hydrothermal reaction;

[0013] Step S4: Place in an oven at 140-160°C for 18-24 h, cool and centrifuge to obtain NH2-MIL-125 material;

[0014] Step S5: treating the powder obtained in step S4 at 100-150° C. for 10-12 h under vacuum to obtain an activated NH2-MIL-125 material;

[0015] Step S6: immersing a certain amount of activated NH2-MIL-125 material obtained in step S5 in an organic solvent containing lithium salt, and continuously stirring for 10-12 hours;

[0016] Step S7: The mixed solution in step S6 is centrifuged, washed and dried at 100-150° C. for 10-12 h under vacuum to obtain the material.

[0017] In an optional scheme: in step S1, the volume ratio of anhydrous methanol to N,N-dimethylformamide is 1:3-4.

[0018] In an optional solution: the lithium salt concentration in step S6 is 1M.

[0019] In an optional solution: the lithium exchange process in step S6 is carried out in a glove box filled with argon, and the content of water and oxygen in the glove box is less than 0.01 ppm.

[0020] A method for preparing the light-assisted solid-state lithium-air battery as described above comprises the following steps:

[0021] Step A1 Preparation of solid electrolyte-light-air cathode integrated material: Mix the photocatalyst NH2-MIL-125 material with the conductive agent as a porous layer, and use the NH2-MIL-125 material as a dense layer, and compact and shape it by cold pressing;

[0022] Step A2: Battery assembly: In a glove box, place the negative electrode lithium sheet, the solid electrolyte-light-air positive electrode integrated material prepared above, and the positive electrode current collector on the negative electrode shell in sequence, and finally assemble the positive electrode shell with holes, and fix the battery on a battery press to obtain a light-assisted solid-state lithium-air battery.

[0023] In an optional solution: in step A1, the photocatalyst NH2-MIL-125 material and the conductive agent are mixed in a ratio of 9:1.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0025] The present invention constructs a solid-state photo-air cathode of ion / electron mixed conductor in lithium-air battery for the first time, designs a photo-assisted solid-state lithium-air battery of electrode-electrolyte integrated material, realizes ultra-low overpotential, high energy conversion efficiency, and safe and stable long-term operation;

[0026] The ion / electron mixed conductor of the present invention uses one material to establish a single conduction path, avoiding the complex path of two materials establishing two paths to conduct electrons and lithium ions respectively. At the same time, when the material is used as a photocatalyst for a battery, it can absorb visible light and generate highly active photogenerated carriers to participate in the battery reaction, thereby improving the positive electrode reaction kinetics;

[0027] The integrated electrode-electrolyte integrated material of the present invention can not only improve the packaging efficiency of the battery through integration, but also reduce the ohmic transmission loss and improve the energy density. The material preparation cost is low, the reaction process is simple, and the process repeatability is good;

[0028] The light-assisted solid-state lithium-air battery of the present invention shows great potential in the application of electric vehicles and portable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of NH2-MIL-125-Li in Example 1 of the present invention.

[0030] Figure 2 This is a first cycle charge and discharge curve diagram of the light-assisted lithium-air battery in Example 1 of the present invention.

[0031] Figure 3 This is a schematic diagram of the structure of a light-assisted solid-state lithium-air battery in Example 2 of the present invention.

[0032] Figure 4 This is a cycle performance diagram of the light-assisted solid-state lithium-air battery in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. The various embodiments listed in the present invention are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any obvious modifications or changes made to the present invention do not depart from the spirit and scope of the present invention.

[0034] Example 1

[0035] This embodiment relates to a light-assisted lithium-air battery with ultra-low charging potential. By introducing a photocatalyst into the lithium-air battery, a light-assisted lithium-air battery is designed to achieve high energy conversion efficiency and conversion and utilization of solar energy;

[0036] Among them, this embodiment relates to a light-assisted lithium-air battery with ultra-low charging potential. By introducing a photocatalyst into the lithium-air battery, a light-assisted lithium-air battery is designed to achieve high energy conversion efficiency and conversion and utilization of solar energy:

[0037] (1) Preparation of photocatalyst:

[0038] First, 0.816 g of 2-aminoterephthalic acid was added into a mixture of anhydrous methanol and N,N-dimethylformamide in a volume ratio of 1:3 under stirring, and the mixture was mixed evenly;

[0039] Slowly add 0.45 mL of isopropyl titanate into the above mixture under stirring, and stir vigorously to obtain a uniform clear mixed solution;

[0040] The obtained mixed solution is transferred to a reactor for hydrothermal reaction;

[0041] The reaction was carried out in an oven at 150°C for 24 hours, and the mixture was centrifuged and washed after cooling to obtain NH2-MIL-125 material. Subsequently, the obtained powder was treated at 120°C for 12 hours under vacuum to obtain activated NH2-MIL-125 material.

[0042] A certain amount of the activated NH2-MIL-125 material obtained was immersed in an organic solvent of lithium hexafluorophosphate / tetraethylene glycol dimethyl ether (1 M) and stirred for 12 h;

[0043] The mixed solution was centrifuged, washed and dried at 120° C. for 12 h under vacuum to obtain the NH2-MIL-125-Li photocatalytic material having both ion and electron conductivity.

[0044] The prepared photocatalyst material has a uniform rounded tetrahedral structure. Figure 1 ;

[0045] (2) Preparation of light-air cathode:

[0046] The super-hydrophilic carbon cloth was ultrasonically cleaned in ethanol, then washed with deionized water, and then dried overnight in an oven at 60° C. The dried carbon cloth was punched into discs with a diameter of 12 mm using a cutter.

[0047] The photocatalyst material and the polyvinylidene fluoride binder were mixed evenly in a mass ratio of 9:1, and then N,N-dimethylformamide was added as a dispersant. The mixed slurry was evenly sprayed on the prepared electrode sheet and placed in a 60°C oven to dry overnight.

[0048] (3) Preparation of electrolyte:

[0049] Weigh 14.354 g of lithium bis(trifluoromethanesulfonyl)imide powder using a balance, dissolve it in 50 mL of tetraethylene glycol dimethyl ether solution, and stir to fully dissolve it. Used as the electrolyte of light-assisted lithium-air battery.

[0050] (4) Battery assembly and testing:

[0051] In a glove box, the negative electrode lithium sheet, the glass fiber diaphragm soaked with electrolyte, the photo-air positive electrode prepared above and the positive electrode current collector are placed on the negative electrode shell in sequence, and finally the positive electrode shell with holes is assembled and the battery is fixed on a battery press to obtain a light-assisted lithium-air battery.

[0052] The assembled battery was taken out of the glove box and quickly transferred to a quartz test bottle, and pure oxygen was introduced to replace the air in the bottle. For the test under dark conditions, a 350W xenon lamp was used to vertically illuminate the photocatalytic cathode with a light intensity of 40 mW / cm 2 .

[0053] The prepared light-assisted lithium-air battery has a low charge and discharge overpotential and ultra-high energy conversion efficiency. −1 When discharging and charging at a current density of 2.79V and 2.97V respectively (such as Figure 2 ), the energy conversion efficiency can reach 94%.

[0054] This embodiment illustrates that the NH2-MIL-125 metal organic framework material with freely movable lithium ions as a photocatalyst for solid-state photo-air cathode can significantly improve the lower charge and discharge overpotential and ultra-high energy conversion efficiency.

[0055] Example 2

[0056] This embodiment relates to a light-assisted solid-state lithium-air battery with ultra-low charging potential. By introducing an ion / electron mixed conductor into the lithium-air battery to construct a solid electrolyte-light-air positive electrode integrated material, a light-assisted solid-state lithium-air battery is designed to achieve high energy conversion efficiency and conversion and utilization of solar energy. The structural schematic diagram of the battery is shown in FIG. Figure 3 As shown, it includes a negative electrode, a solid electrolyte layer, and a solid light-air positive electrode layer.

[0057] The method for preparing the light-assisted solid-state lithium-air battery of this embodiment specifically comprises the following steps:

[0058] (1) Preparation of solid electrolyte-light-air cathode integrated materials:

[0059] First, 0.816 g of 2-aminoterephthalic acid was added to a mixture of anhydrous methanol and N,N-dimethylformamide in a volume ratio of 1-3:4 under stirring, and mixed evenly;

[0060] Slowly add 0.45 mL of isopropyl titanate into the above mixture under stirring, and stir vigorously to obtain a uniform clear mixed solution;

[0061] The obtained mixed solution is transferred to a reactor for hydrothermal reaction; placed in an oven at 140-160° C. for reaction for 18-24 hours, cooled and centrifuged for washing to obtain NH2-MIL-125 material;

[0062] Subsequently, the obtained powder is treated at 100-150° C. for 10-12 h under vacuum to obtain an activated NH2-MIL-125 material;

[0063] Immerse a certain amount of the activated NH2-MIL-125 material obtained in an organic solvent of lithium hexafluorophosphate / tetraethylene glycol dimethyl ether (1 M) and continue stirring for 10-12 hours;

[0064] The mixed solution is centrifuged, washed and dried at 100-150° C. for 10-12 hours under vacuum to obtain the NH2-MIL-125-Li photocatalytic material having both ion / electron conductivity.

[0065] The obtained catalyst and conductive agent were mixed in a ratio of 9:1 as a porous layer, and NH2-MIL-125-Li was used as a dense layer, and compacted into a shape by cold pressing.

[0066] (2) Battery assembly and testing:

[0067] In a glove box, the negative electrode lithium sheet, the above-prepared solid electrolyte-light-air positive electrode integrated material and the positive electrode current collector are placed on the negative electrode shell in sequence, and finally the positive electrode shell with holes is assembled and the battery is fixed on a battery press to obtain a light-assisted solid-state lithium-air battery.

[0068] The assembled battery was taken out of the glove box and quickly transferred to a quartz test bottle, and pure oxygen was introduced to replace the air in the bottle. For the test under dark conditions, a 350W xenon lamp was used to vertically illuminate the photocatalytic cathode with a light intensity of 40mW / cm 2 .

[0069] The prepared light-assisted lithium-air battery can stably cycle more than 60 times at a low charge and discharge overpotential. −1 The current density of the discharge and charge cycle test curve is as follows Figure 4 shown.

[0070] The above is only a specific implementation of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A light-assisted solid-state lithium-air battery, comprising a negative electrode lithium sheet, a solid electrolyte layer and a solid light-air positive electrode layer, characterized in that: The solid-state photo-air cathode layer is supported by ion / electron conductive materials and uses NH2-MIL-125 metal-organic framework material with freely moving lithium ions in the pores as a photocatalyst. The solid-state electrolyte layer is made of NH2-MIL-125 metal-organic framework material with freely moving lithium ions, and forms a solid-state electrolyte-photo-air cathode integrated material with the solid-state photo-air cathode layer.

2. The light-assisted solid-state lithium-air battery according to claim 1, characterized in that: The NH2-MIL-125 metal organic framework material with freely movable lithium ions is prepared by exchanging an activated NH2-MIL-125 material, that is, an NH2-MIL-125 material with open metal sites, in a lithium salt solution.

3. The light-assisted solid-state lithium-air battery according to claim 1, characterized in that: The NH2-MIL-125 material is prepared by a hydrothermal method, which specifically includes the following steps: Step S1: adding a certain amount of 2-aminoterephthalic acid to a mixture of anhydrous methanol and N,N-dimethylformamide under stirring, and mixing evenly; Step S2: slowly adding a certain amount of isopropyl titanate into the above-mentioned mixed solution under stirring, and vigorously stirring to obtain a uniform clear mixed solution; Step S3: transferring the mixed solution obtained in step S2 to a reactor for hydrothermal reaction; Step S4: Place in an oven at 140-160°C for 18-24 h, cool and centrifuge to obtain NH2-MIL-125 material; Step S5: treating the powder obtained in step S4 at 100-150° C. for 10-12 h under vacuum to obtain an activated NH2-MIL-125 material; Step S6: immersing a certain amount of activated NH2-MIL-125 material obtained in step S5 in an organic solvent containing lithium salt, and continuously stirring for 10-12 hours; Step S7: The mixed solution in step S6 is centrifuged, washed and dried at 100-150° C. for 10-12 h under vacuum to obtain the material.

4. The light-assisted solid-state lithium-air battery according to claim 3, characterized in that: In step S1, the volume ratio of anhydrous methanol to N,N-dimethylformamide is 1:3-4.

5. The light-assisted solid-state lithium-air battery according to claim 3, characterized in that: The lithium salt concentration in step S6 is 1M.

6. The light-assisted solid-state lithium-air battery according to claim 3, characterized in that: The lithium exchange process in step S6 is carried out in a glove box filled with argon gas, and the content of water and oxygen in the glove box is less than 0.01 ppm.

7. A method for preparing a light-assisted solid-state lithium-air battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step A1 Preparation of solid electrolyte-light-air cathode integrated material: Mix the photocatalyst NH2-MIL-125 material with the conductive agent as a porous layer, and use the NH2-MIL-125 material as a dense layer, and compact and shape it by cold pressing; Step A2: Battery assembly: In a glove box, place the negative electrode lithium sheet, the solid electrolyte-light-air positive electrode integrated material prepared above, and the positive electrode current collector on the negative electrode shell in sequence, and finally assemble the positive electrode shell with holes, and fix the battery on a battery press to obtain a light-assisted solid-state lithium-air battery.

8. The method for preparing a light-assisted solid-state lithium-air battery according to claim 7, characterized in that: In the step A1, the photocatalyst NH2-MIL-125 material and the conductive agent are mixed in a ratio of 9:1.